Support for Character Education-Based Literary Projects and Digital Promotion Through Crowdfunding: Pendampingan Proyek Sastra Berbasis Pendidikan Karakter Dan Promosi Digital Melalui Crowdfunding - Yuliana Sari; Nadia Amelia Elyana Poluan; Ika Febriana; Anggi Rahmawati; Elvi Susana Dalimunthe; Raudhatul Amaliyah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This community service activity aims to improve the short story writing skills, creativity, and abilities of members of the Smart Route Community Reading Park (TBM) in designing and utilizing crowdfunding as a financing strategy for the publication of literary works. This was done to address the main problems of partners in terms of low creative writing skills and the suboptimal use of digital technology for publication and marketing of works. This program was implemented through three stages: training in writing short stories based on character values ​​and local wisdom, training in digital promotion and introduction to crowdfunding, and mentoring in completing the manuscript of a short story anthology for publication. The results of the activity showed significant improvements in aspects of writing skills and digital literacy. However, the final product, the anthology manuscript, is not yet fully ready for publication and therefore cannot be marketed digitally or through crowdfunding. Nevertheless, the competence of participants in writing techniques, editing, and the use of digital media has significantly increased. This program contributes to building a culture of productive literacy and creative character in the TBM environment.